Analysis of MSME Marketing Challenges in Showing Its Existence Towards Export Scale Case Study on AMMIC - Muhyiddin Zainul Arifin; Achmadi Achmadi (INCOME: Innovation of Economics and Management, 2022)
The challenge of export-scale marketing carried out by MSMEs that can increase sales and increase competitiveness with the SWOT analysis method in the AMMIC business (Association of Creative Mandiri Partners). The selection of the location of this research was carried out by looking at the development of MSMEs in the current era, the growing development of MSMEs in Indonesia, the business actors dared to take opportunities and decisions by exporting their products abroad aimed at developing the economy and introducing local products. The analysis used to determine the marketing challenges of MSMEs on an export scale in the AMMIC business (Association of Independent IKM Creative Partners) includes evaluation of internal factors, evaluation of external factors, IFAS matrix, EFAS matrix, SWOT matrix and Grand Strategy matrix.